2016
DOI: 10.4028/www.scientific.net/msf.879.1437
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Inhomogeneous Layered Microstructure

Abstract: Multipass friction stir processing (FSP) technique was used to get inhomogeneous layered microstructure in Al 5086 alloy. Different proportions of fine and coarse grain microstructures were generated using FSP. In the present work, material with inhomogeneous layered microstructure generated using FSP was subjected to deformation at temperature of 500°C and at strain rate in the range of 5×10-4 to 1×10-2 s-1. It was observed that the inhomogeneous layered microstructure with more than 50% fine grain microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However in Al alloys, inhomogeneous microstructure has shown to exhibit higher ductility than homogeneous fine-grained microstructure [74][75][76]87]. Pancholi et al [90] demonstrated that at least 50% fine grain microstructure is required in the Al 5086 alloy for it to exhibit superior superplasticity when compared to the homogeneous fine-grained material. It was argued that microstructural refinement in the remaining 50% of coarse-grained microstructure, which leads to fully homogenous microstructure in the material, was the reason for higher superplasticity [84,87].…”
Section: Illustration Of Nano-twin Formation During Superplastic Defomentioning
confidence: 99%
“…However in Al alloys, inhomogeneous microstructure has shown to exhibit higher ductility than homogeneous fine-grained microstructure [74][75][76]87]. Pancholi et al [90] demonstrated that at least 50% fine grain microstructure is required in the Al 5086 alloy for it to exhibit superior superplasticity when compared to the homogeneous fine-grained material. It was argued that microstructural refinement in the remaining 50% of coarse-grained microstructure, which leads to fully homogenous microstructure in the material, was the reason for higher superplasticity [84,87].…”
Section: Illustration Of Nano-twin Formation During Superplastic Defomentioning
confidence: 99%